ISSUES OF PRODUCT EXPORT OF SMALL BUSINESS AND ENTREPRENEURIAL ENTITIES (World Economics and Finance Bulletin, 2022)
This article talks about the reforms implemented in the formation of a stable and effective economy in our country and their results and the impact of export and import on them.
Keywords: Small business; entrepreneurship; import; export